Numerical Modelling of Surface Water Wave Interaction with a Moving Wall (Communications in Computational Physics, 2018)
In the present manuscript we consider the practical problem of wave interactionwith a vertical wall. However, the novelty here consists in the fact that the wallcan move horizontally due to a system of springs. The water wave evolution is describedwith the free surface potential flow model. Then, a semi-analytical numericalmethod is presented. It is based on a mapping technique and a finite difference schemein the transformed domain. The idea is to pose the equations on a fixed domain. Thismethod is thoroughly tested and validated in our study. By choosing specific values ofspring parameters, this system can be used to damp (or in other words to extract theenergy of) incident water waves.
Keywords: Wave/body interaction; full Euler equations; movable wall; wave run-up; wave damping; wave energy extraction.